A blended psychological intervention for postpartum depression: acceptability and preferences in women presenting depressive symptoms. (1st January 2023) - Branquinho, Mariana; Canavarro, Maria Cristina; Fonseca, Ana
ABSTRACT: Objectives: To evaluate the acceptability of and preferences for a blended psychological intervention (combining face-to-face sessions and web-based interventions) for the treatment of postpartum depression among Portuguese women presenting depressive symptoms and to explore the factors associated with its acceptability. Background: Despite its high prevalence and the existence of effective treatment, still few women seek professional help for postpartum depression, demanding for new treatment formats, such as blended interventions. Methods: Women (n = 235) presenting postpartum depressive symptoms (EPDS>9) completed an internet survey assessing sociodemographic and clinical information, depressive symptoms, e-health literacy and the acceptability of and preferences for a blended intervention for postpartum depression. Results: Most of the participants considered a blended intervention for postpartum depression to be useful and would be available to use it. Women reported significantly more advantages than disadvantages in regard to this treatment format. Married women, employed, with younger babies and with less severe depressive symptoms had a higher likelihood of finding a blended intervention useful. Higher educational levels increased the likelihood of being available to obtain a blended treatment. Most participants preferred an equal distribution of content across face-to-face and online sessions. Approximately one-third of the sample preferred a 75% face-to-face/ 25% online proportion. Most of the women preferred a duration of 45–60 minutes for face-to-face sessions and 30–45 minutes for online sessions. Conclusion: Our findings support and inform the development of blended psychological treatments for postpartum depression, according to women's preferences, and highlight the prioritisation of this format according to women's characteristics.